Bidding strategies for multi-microgrid markets taking into account risk indicators - Lv, Xiangyv; Qi, Chenglong; Ji, Xiu; Yv, Jiqing; Wang, Hui; Han, Huanhuan (Frontiers in Smart Grids, 2024)
A large proportion of new energy generation is integrated into the power grid, making it difficult for the power grid system to maintain reliable, stable, and efficient operation. In order to address these challenges, this paper proposes a multiple microgrid hierarchical optimization structure based on energy routers as the core equipment for energy regulation within microgrids. Considering the uncertainty of renewable energy generation within microgrids, a two-layer energy management bidding strategy based on risk indicators is further proposed. In the process of trading, with the goal of maximizing comprehensive economy, the energy trading model of the distribution network center and energy router is divided into two sub objectives for solving. In the first stage, based on the interests and energy supply and demand relationships of each microgrid, a risk assessment model considering wind and solar uncertainty is established to determine the risk preferences and expected returns of each microgrid. In the second stage, the original problem is decomposed into two subproblems: the minimum cost sub-problem and the maximum transaction volume sub-problem. And an asymmetric bargaining mechanism is adopted to determine the production and sales payment of the microgrid containing energy routers based on the contribution values of energy routers in each microgrid. Finally, the rationality and effectiveness of energy routers as an intelligent decision-maker in energy optimization are verified in a 3-node system.